Operational Efficiency and Leverage Effects in Driving Financial Performance: Firm Size Moderating in Indonesian Chemical Industry (Universitas Islam Kadiri, 2026)
Introduction/Main Objectives: Financial performance in Indonesia’s chemical subsector fluctuated during 2020–2024. Therefore, this study examines the effects of operational efficiency (BOPO) and leverage (DER) on financial performance (ROA), with firm size as a moderating variable. Novelty: This paper adds novelty by testing firm size as a moderating variable in the relationships among operational efficiency (BOPO), leverage (DER), and financial performance (ROA), specifically in IDX-listed chemical subsector firms (2020–2024), thereby addressing gaps and inconsistent results in prior studies. Research Methods: A quantitative causal method with secondary data from annual reports/financial statements of 10 IDX-listed chemical subsector companies (2020–2024), selected using purposive sampling. Analysis uses multiple regression and Moderated Regression Analysis (MRA) in SPSS. Finding/Results: BOPO does not have a significant direct effect on ROA. DER significantly affects ROA with a negative direction. Firm size significantly moderates the BOPO-ROA relationship. Firm size does not moderate the relationship between DER and ROA. Leverage decisions are more consistently related to profitability in the chemical subsector, while the impact of operating efficiency on profitability depends on company scale (larger vs. smaller asset bases), indicating heterogeneous cost–performance dynamics across firm sizes. Conclusion: The study concludes that leverage (DER) influences ROA, while BOPO does not show a consistent direct effect. Firm size moderates the BOPO–ROA relationship but does not moderate the DER–ROA relationship.